Polylactic acid block copolymer and preparation method and application thereof

By combining polylactic acid block copolymers with bio-based additives, the mechanical properties and degradability of polylactic acid materials have been improved, solving the problems of brittleness and degradation rate control of traditional polylactic acid materials in the field of agricultural mulch film, and realizing the preparation of high-performance biodegradable mulch film.

CN121136040AActive Publication Date: 2025-12-16GUANGDONG LINGNAN HEALTH ECOLOGICAL TECH GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511689831.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2025-12-16
Estimated Expiration
2045-11-18

AI Technical Summary

Technical Problem

Existing polylactic acid materials have shortcomings in terms of mechanical properties and biodegradability, especially in the field of agricultural mulch film, where it is difficult to balance the mechanical support for mechanized film laying with the controllability of degradation rate.

Method used

By using polylactic acid block copolymers, combining polylactic acid segments and polyurethane segments, and utilizing oleic acid/linoleic acid long-chain alkyl groups to improve brittleness, and adding bio-derived additives such as citrus fruit peel powder and chitosan to regulate crystallinity, materials with excellent mechanical properties and controllable degradability are prepared.

Benefits of technology

A polylactic acid block copolymer with excellent mechanical properties and controllable degradability was obtained, which solved the shortcomings of traditional polylactic acid materials in terms of mechanical properties and degradability, and is suitable for the application of degradable mulch films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention discloses a polylactic acid block copolymer with excellent mechanical properties and degradability, the structure of the block copolymer contains a polylactic acid chain segment and a polyurethane chain segment, and the preparation raw materials of the polyurethane chain segment are L-lysine diisocyanate and glycerol monooleate / glycerol monolinoleate, all chain segments in the block copolymer have excellent degradability, the block copolymer has high molecular weight and crystallinity, long-chain alkyl of oleic acid / linoleic acid can integrate the brittleness of polylactic acid chain segments, and the block copolymer can be endowed with excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of high molecular copolymer, and particularly relates to a polylactic acid block copolymer with excellent mechanical properties and degradability, a preparation method thereof and application thereof. BACKGROUND

[0002] As a biobased degradable polymer material, polylactic acid (PLA) has been widely used in packaging, fiber and disposable products. Its raw material is derived from renewable plant resources, and the degradation product is harmless to the environment, which meets the requirements of green circular economy development. However, the traditional polylactic acid material has obvious shortcomings: high brittleness, poor toughness, low impact resistance and elongation at break, which seriously limits its in-depth application in fields requiring high mechanical strength and flexibility, such as durable packaging, engineering plastics and agricultural mulching film.

[0003] At present, in order to improve the mechanical properties of polylactic acid, the method of blending modification is usually used, such as physical blending with plasticizer or other polymers (such as polybutylene adipate terephthalate, PBAT). However, this method has obvious disadvantages: the compatibility of the blending system is poor, and phase separation easily occurs, resulting in insufficient long-term use stability of the material and large fluctuation of the mechanical properties; at the same time, the added non-degradable components may delay the overall degradation rate, or produce microplastic residues during the degradation process, affecting its application under strict environmental requirements.

[0004] In particular, in the field of agricultural mulching film, polylactic acid mulching film is concerned due to its degradable characteristics. However, the existing polylactic acid mulching film generally has the problems of insufficient flexibility, poor weather resistance and the like, and it is difficult to meet the needs of mechanical support for film laying and controllability of degradation rate, which has an adverse effect on the ecological environment of farmland and crop yield.

[0005] Therefore, it is a technical problem to be solved in the field to develop a new type of copolymerized polylactic acid with excellent mechanical properties and controllable degradation characteristics. SUMMARY

[0006] In view of the above-mentioned deficiencies in the prior art, a polylactic acid block copolymer with excellent mechanical properties and degradability is provided. The block copolymer contains polylactic acid segments and polyurethane segments in its structure, all of which have excellent degradability, and the block copolymer has high molecular weight and crystallinity. The long-chain alkyl of oleic acid / linoleic acid can also integrate the brittleness of the polylactic acid segment, and can give the block copolymer excellent mechanical properties.

[0007] The first object of the present application is to provide a polylactic acid block copolymer, which comprises a product obtained by reacting a polymer represented by formula (I) with an oligomer represented by formula (II);

[0008] Formula (I) is shown in the following formula (I);

[0009] Formula (II) is shown in the following formula (II);

[0010] The weight average molecular weight of the polymer shown in formula (I) is 3kDa~100kDa;

[0011] In formula (II), R represents the residue after removing one H atom from the carboxyl group in the oleic acid / linoleic acid molecule, and the number average molecular weight of the oligomer shown in formula (II) is 500~2000Da.

[0012] For the above-mentioned polylactic acid block copolymer, firstly, it contains polylactic acid segment, L-lysine diisocyanate and glycerol monooleate / glycerol monolinoleate generated polyurethane segment in structure, wherein the polylactic acid segment and the polyurethane segment both have degradability, thus the polylactic acid block copolymer has excellent degradability; secondly, the isocyanate groups at the ends of the oligomer shown in formula (II) can react with the hydroxyl groups and carboxyl groups at the ends of the polylactic acid shown in formula (I), the oligomer shown in formula (II) actually plays the role of a large chain extender, which can increase the molecular weight of the system without destroying the crystalline structure of the polylactic acid, so that the polylactic acid block copolymer has good mechanical strength, at the same time, the long-chain alkyl groups in the polyurethane segment can also integrate the brittleness of the polylactic acid segment, so that the polylactic acid block copolymer is both strong and tough, and has excellent mechanical properties.

[0013] In some embodiments of the present application, the polymer shown in formula (I) includes at least one of PLLA and PDLA.

[0014] In some embodiments of the present application, the preparation raw material of the oligomer shown in formula (II) is L-lysine diisocyanate and glyceride in a molar ratio of 1.5~2.5:1, and the glyceride is at least one of glycerol monooleate and glycerol monolinoleate.

[0015] In some embodiments of the present application, the preparation method of the oligomer shown in formula (II) includes the following steps: adding L-lysine diisocyanate into glyceride, and reacting at 55~85℃ for 1~5h until the NCO value is almost unchanged, to obtain the oligomer shown in formula (II).

[0016] In some embodiments of the present application, the preparation method of the oligomer shown in formula (II) further includes the step of adding a catalyst before the reaction.

[0017] In some embodiments of the present application, the preparation method of the oligomer shown in formula (II), the catalyst is an organic tin catalyst or an organic titanium catalyst.

[0018] In some embodiments of the present application, the amount of the catalyst used in the preparation method of the oligomer of formula (II) is 0.05-1 wt% of L-lysine diisocyanate.

[0019] In some embodiments of the present application, the mass ratio of the polymer of formula (I) to the oligomer of formula (II) is 100:0.1-20. By controlling the mass ratio of the two within the above range, the crystallinity of the polylactic acid block copolymer is maintained, thereby obtaining better mechanical properties.

[0020] The second object of the present application is to provide a preparation method of the polylactic acid block copolymer, comprising the following steps: mixing the polymer of formula (I) with the oligomer of formula (II), reacting at 50-85°C for 2-24h, and then performing a purification step to obtain the polylactic acid block copolymer.

[0021] In some embodiments of the present application, the purification step comprises at least one of filtration, washing, dissolution, and precipitation.

[0022] In some embodiments of the present application, the preparation method of the polylactic acid block copolymer further comprises a step of adding a catalyst before the reaction.

[0023] In some embodiments of the present application, the catalyst used in the preparation method of the polylactic acid block copolymer is an organic tin or organic titanium catalyst.

[0024] In some embodiments of the present application, the amount of the catalyst used in the preparation method of the polylactic acid block copolymer is 0.05-2 wt% of the polymer of formula (I).

[0025] The third object of the present application is to provide a degradable composition comprising the polylactic acid block copolymer and a biological additive; the biological additive comprises citrus fruit peel powder. By adding the biological additive such as citrus fruit peel powder to the degradable composition, the biocompatibility and degradability of the degradable composition are improved while ensuring environmental protection. Meanwhile, the main components of the citrus fruit peel powder are pectin, cellulose, lignin, and limonin, which can regulate the crystallinity of the polylactic acid segment, thereby improving the mechanical properties of the degradable composition.

[0026] In some embodiments of the present application, the mass ratio of the polylactic acid block copolymer to the biological additive is 100:5-80. By controlling the mass ratio of the two within the above range, both excellent mechanical properties and degradability are obtained.

[0027] In some embodiments of the present application, the citrus fruit peel in the citrus fruit peel powder is at least one selected from the group consisting of orange peel, lemon peel, grapefruit peel, and tangerine peel.

[0028] In some embodiments of the present application, the preparation method of the citrus fruit peel powder comprises the following steps: washing, chopping, freeze-drying, grinding, and sieving the citrus fruit peel.

[0029] In some embodiments of the present application, the bio-source additive further comprises chitosan. Chitosan is a natural high-molecular amino polysaccharide, which can interact with the citrus fruit peel powder to jointly regulate the crystallinity of the polylactic acid segment, thereby further improving the mechanical properties of the degradable composition.

[0030] In some embodiments of the present application, the mass ratio of the citrus fruit peel powder to the chitosan is 1:0.1-1. By controlling the mass ratio of the two in the reaction, the degradable composition can obtain excellent mechanical properties.

[0031] In some embodiments of the present application, the bio-source additive further comprises at least one of microcrystalline cellulose, nanocellulose, and starch, and the mass ratio of the bio-source additive to the citrus fruit peel powder is 0.1-1:1.

[0032] The fourth object of the present application is to provide the polylactic acid block copolymer or the degradable composition described above for use in preparing a degradable mulch film.

[0033] The fifth object of the present application is to provide a degradable mulch film comprising the polylactic acid block copolymer or the degradable composition described above.

[0034] Compared with the prior art, the present application has the following beneficial effects:

[0035] (1) The polylactic acid block copolymer of the present application has a relatively large molecular weight, and contains a polylactic acid segment and a polyurethane segment with degradability in structure. Moreover, the embedded polyurethane segment does not destroy the crystalline structure of the polylactic acid, and also integrates the brittleness of the polylactic acid segment, so that a polylactic acid block copolymer with excellent mechanical properties and degradability can be obtained.

[0036] (2) The preparation method of the polylactic acid block copolymer in the present application is simple and controllable, which is conducive to ensuring the performance stability of products of different batches.

[0037] (3) The preparation raw materials of the polylactic acid block copolymer, the degradable composition, and the degradable mulch film in the present application are green in origin, which conforms to the concept of green environmental protection. DETAILED DESCRIPTION

[0038] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.

[0039] Unless otherwise specified, all raw materials used in this invention are derived from commercially available products and are expressed in parts by weight.

[0040] The following preparation examples are used to prepare oligomers as shown in formula (II).

[0041] Preparation Example 1

[0042] This preparation example provides a method for preparing oligomer O1 represented by formula (II), which includes the following steps:

[0043] 45.25 parts of L-lysine diisocyanate and 0.02 parts of dibutyltin dilaurate were added to 35.65 parts of dried glycerol monooleate. The mixture was reacted at 70°C for 2 hours until the NCO value remained constant, yielding oligomer O1 as shown in formula (II). The NCO content at the end of oligomer O1 was determined by titration, and its number-average molecular weight was found to be 912 Da.

[0044] Preparation Example 2

[0045] This preparation example provides a method for preparing the oligomer O2 represented by formula (II), which includes the following steps:

[0046] 45.25 parts of L-lysine diisocyanate and 0.02 parts of dibutyltin dilaurate were added to 35.45 parts of dried glycerol monolinoleate. The mixture was reacted at 70°C for 2 hours until the NCO value remained constant, yielding oligomer O2 as shown in formula (II). The NCO content at the end of oligomer O2 was determined by titration, and its number-average molecular weight was found to be 850 Da.

[0047] Preparation Example 3

[0048] This preparation example provides a method for preparing oligomer O3 represented by formula (II), which includes the following steps:

[0049] 45.25 parts of L-lysine diisocyanate and 0.02 parts of dibutyltin dilaurate were added to 17.83 parts of dried glycerol monooleate and 17.73 parts of dried glycerol monolinoleate. The mixture was reacted at 70°C for 2 hours until the NCO value remained constant, yielding oligomer O3 as shown in formula (II). The NCO content at the end of oligomer O3 was determined by titration, and its number-average molecular weight was found to be 958 Da.

[0050] The following examples are used to prepare polylactic acid block copolymers.

[0051] Example 1

[0052] This embodiment provides a method for preparing polylactic acid block copolymer CP1, comprising the following steps: 100 parts of dried PLLA (model DG-LOH030, from Jinan Daigang Biotechnology) are mixed with 0.5 parts of oligomer O1 prepared in Preparation Example 1 above, and 0.5 parts of dibutyltin dilaurate are added. The mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP1.

[0053] Example 2

[0054] This embodiment provides a method for preparing polylactic acid block copolymer CP2, comprising the following steps: 100 parts of dried PLLA (model DG-LOH030) are mixed with 5 parts of oligomer O2 prepared in Preparation Example 2 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP2.

[0055] Example 3

[0056] This embodiment provides a method for preparing polylactic acid block copolymer CP3, comprising the following steps: 100 parts of dried PLLA (model DG-LOH030) are mixed with 15 parts of oligomer O3 prepared in Preparation Example 3 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP3.

[0057] Example 4

[0058] This embodiment provides a method for preparing polylactic acid block copolymer CP4, comprising the following steps: 100 parts of dried PLLA (model DG-LOH070) are mixed with 5 parts of oligomer O1 prepared in Preparation Example 1 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP4.

[0059] Example 5

[0060] This embodiment provides a method for preparing polylactic acid block copolymer CP5, comprising the following steps: 100 parts of dried PLLA (model DG-LOH100) are mixed with 5 parts of oligomer O1 prepared in Preparation Example 1 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP5.

[0061] Example 6

[0062] This embodiment provides a method for preparing polylactic acid block copolymer CP6, comprising the following steps: 100 parts of dried PDLA (model DG-DOH070) are mixed with 5 parts of oligomer O1 prepared in Preparation Example 1 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP6.

[0063] Example 7

[0064] This embodiment provides a method for preparing polylactic acid block copolymer CP7, comprising the following steps: 50 parts of dried PLLA (model DG-LOH070) and 50 parts of dried PDLA (model DG-DOH070) are mixed with 5 parts of oligomer O1 prepared in Preparation Example 1 above, 0.5 parts of dibutyltin dilaurate are added, and the mixture is reacted at 60°C for 5 hours. The resulting product is dissolved in dichloromethane, precipitated with methanol, filtered, and dried to obtain polylactic acid block copolymer CP7.

[0065] The following application examples and comparative application examples are used to prepare biodegradable compositions.

[0066] Application Example 1

[0067] This application example provides a biodegradable composition C1, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4 and 10 parts of grapefruit peel powder. The preparation method is as follows:

[0068] (1) Chop, freeze-dry, grind, and pass through a 100-mesh sieve to obtain grapefruit peel powder;

[0069] (2) The polylactic acid block copolymer CP4 obtained in Example 4 after drying was thoroughly mixed with the above grapefruit peel powder in parts by weight to obtain a biodegradable composition C1.

[0070] Application Example 2

[0071] This application example provides a biodegradable composition C2, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4 and 30 parts of grapefruit peel powder. The preparation method is the same as that in Application Example 1.

[0072] Application Example 3

[0073] This application example provides a biodegradable composition C3, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4 and 50 parts of grapefruit peel powder. The preparation method is the same as that in Application Example 1.

[0074] Application Example 4

[0075] This application example provides a biodegradable composition C4, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4 and 30 parts of orange peel powder. The preparation method is as follows:

[0076] (1) Chop orange peel, freeze-dry, grind, and pass through a 100-mesh sieve to obtain orange peel powder;

[0077] (2) The polylactic acid block copolymer CP4 obtained in Example 4 after drying was thoroughly mixed with the orange peel powder in parts by weight to obtain the biodegradable composition C4.

[0078] Application Example 5

[0079] This application example provides a biodegradable composition C5, which is prepared from 100 parts of polylactic acid block copolymer CP4 obtained in Example 4 and 30 parts of chitosan. The preparation method is as follows: the polylactic acid block copolymer CP4 obtained in Example 4 after drying is thoroughly mixed with chitosan (from Aladdin, catalog number C299272) with a degree of deacetylation ≥75% in parts by weight to obtain biodegradable composition C5.

[0080] Application Example 6

[0081] This application example provides a biodegradable composition C6, which is prepared from 100 parts of polylactic acid block copolymer CP4 obtained in Example 4 and 30 parts of microcrystalline cellulose. The preparation method is as follows: the polylactic acid block copolymer CP4 obtained in Example 4 after drying is thoroughly mixed with microcrystalline cellulose (from Qufu Tianli) in parts by weight to obtain biodegradable composition C6.

[0082] Application Example 7

[0083] This application example provides a biodegradable composition C7, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4, 20 parts of grapefruit peel powder, and 10 parts of chitosan. The preparation method is as follows:

[0084] (1) Chop, freeze-dry, grind, and pass through a 100-mesh sieve to obtain grapefruit peel powder;

[0085] (2) The polylactic acid block copolymer CP4 obtained in Example 4 after drying was thoroughly mixed with the above grapefruit peel powder and chitosan with a degree of deacetylation ≥75% (from Aladdin, catalog number C299272) in parts by weight to obtain the biodegradable composition C7.

[0086] Application Example 8

[0087] This application example provides a biodegradable composition C8, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4, 20 parts of grapefruit peel powder, and 10 parts of microcrystalline cellulose. The preparation method is as follows:

[0088] (1) Chop, freeze-dry, grind, and pass through a 100-mesh sieve to obtain grapefruit peel powder;

[0089] (2) The polylactic acid block copolymer CP4 obtained in Example 4 after drying was thoroughly mixed with the above grapefruit peel powder and microcrystalline cellulose (from Qufu Tianli) in parts by weight to obtain the biodegradable composition C8.

[0090] Application Example 9

[0091] This application example provides a biodegradable composition C9, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4, 10 parts of grapefruit peel powder, and 20 parts of chitosan, with the other ingredients being consistent with Application Example 7.

[0092] Application Example 10

[0093] This application example provides a biodegradable composition C10, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4, 15 parts of grapefruit peel powder, and 15 parts of chitosan, with the other ingredients being consistent with Application Example 7.

[0094] Application Example 11

[0095] This application example provides a biodegradable composition C11, which is prepared from 100 parts of the polylactic acid block copolymer CP4 obtained in Example 4, 25 parts of grapefruit peel powder, and 5 parts of chitosan, with the other ingredients being consistent with Application Example 7.

[0096] Comparative Application Example 1

[0097] This application example provides a biodegradable composition CC1, which is prepared from 100 parts of PLLA and 30 parts of grapefruit peel powder, and the preparation method is as follows:

[0098] (1) Chop, freeze-dry, grind, and pass through a 100-mesh sieve to obtain grapefruit peel powder;

[0099] (2) The dried PLLA (model DG-LOH070) is thoroughly mixed with the above grapefruit peel powder in parts by weight to obtain the biodegradable composition CC1.

[0100] Performance testing:

[0101] 1. Molecular weight

[0102] The weight-average molecular weights of PLLA (model DG-LOH070) and the polylactic acid block copolymers CP1-CP7 obtained in Examples 1-7 were determined using Waters GPC, THF as solvent, and PS as standard. The results are shown in Table 1.

[0103] 2. Mechanical properties

[0104] Referring to GB13022-91, the mechanical properties of type II dumbbell specimens made of PLLA (model DG-LOH070), polylactic acid block copolymers CP1-CP7 obtained in Examples 1-7, biodegradable compositions C1-C11 obtained in Application Examples 1-11, and biodegradable composition CC1 obtained in Comparative Application Example 1 were determined at room temperature, with a tensile speed of 5 mm / min. The results are shown in Table 1.

[0105] 3. Degradability

[0106] Using a blown film machine, films with a thickness of 16 μm were made from PLLA (model DG-LOH070), polylactic acid block copolymer CP4 obtained in Example 4, biodegradable compositions C1-C11 obtained in Application Examples 1-11, and biodegradable composition CC1 obtained in Comparative Application Example 1. Five films with a size of 10 cm × 10 cm were taken, placed in a mesh nylon bag with a large mesh opening, and sealed. The bags were dried at 50 °C for 5 hours to obtain test samples, and the mass m0 at this time was recorded. The test samples were buried at a depth of 30 cm in the company's green lawn (the mass ratio of soil to farmyard manure was 5:1) where farmyard manure (chicken manure) had been applied. Each group of test samples had 4 samples, which were weighed on the 7th, 20th, 60th, and 100th days after burying the soil (the test samples were cleaned and dried at 50 °C before weighing), and the obtained masses were m7, m... 20 m 60 m 100 According to [m7 (or m) 20 m 60 m 100 The degradation rate was calculated by multiplying [m0] by 100% after different numbers of days of natural composting. The results are shown in Table 1. Furthermore, the appearance of the mesh nylon bag remained almost unchanged throughout the entire process.

[0107] Table 1

[0108]

[0109] As shown in Table 1, the polylactic acid block copolymer of the present invention has superior mechanical strength, elongation at break, and biodegradability compared to ordinary polylactic acid. The biodegradable composition prepared by the polylactic acid block copolymer of the present invention and a bio-derived additive including citrus fruit peel powder not only has higher mechanical strength but also has biodegradability comparable to that of the polylactic acid block copolymer. In particular, when the bio-derived additive includes a certain mass ratio of citrus fruit peel powder and chitosan, higher mechanical strength can be obtained.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that after reading this application specification, they can still modify or make equivalent substitutions to the specific implementation of the present invention, but these modifications or changes do not depart from the protection scope of the pending claims of the present invention.

Claims

1. A polylactic acid block copolymer, characterized in that, The polylactic acid block copolymer comprises the product obtained by reacting the polymer of formula (I) with the oligomer of formula (II); Equation (I); Formula (II); Among them, the weight-average molecular weight of the polymer shown in formula (Ⅰ) is 3kDa~100kDa; In formula (II), R represents the residue after removing one H atom from the carboxyl group in the oleic acid / linoleic acid molecule, and the number average molecular weight of the oligomers shown in formula (II) is 500~2000 Da.

2. The polylactic acid block copolymer according to claim 1, characterized in that, The polymer represented by formula (Ⅰ) includes at least one of PLLA and PDLA.

3. The polylactic acid block copolymer according to claim 1, characterized in that, The raw materials for preparing the oligomer shown in formula (II) are L-lysine diisocyanate and glycerol ester in a molar ratio of 1.5 to 2.5:

1. The glyceride is at least one of glyceryl monooleate and glyceryl monolinoleate.

4. The polylactic acid block copolymer according to claim 1, characterized in that, The mass ratio of the polymer represented by formula (I) to the oligomer represented by formula (II) is 100:0.1~20.

5. The method for preparing the polylactic acid block copolymer according to any one of claims 1 to 4, characterized in that, The polymer represented by formula (I) is mixed with the oligomer represented by formula (II) and reacted at 50-85°C for 2-24 hours, followed by purification steps to obtain the polylactic acid block copolymer.

6. A biodegradable composition, characterized in that, Includes the polylactic acid block copolymer according to any one of claims 1 to 4, and bio-based additives; The bio-based additives include citrus fruit peel powder.

7. The biodegradable composition according to claim 6, characterized in that, The mass ratio of the polylactic acid block copolymer to the bio-based additive is 100:5~80.

8. The biodegradable composition according to claim 6, characterized in that, The bio-derived additives also include chitosan.

9. The use of the polylactic acid block copolymer according to any one of claims 1 to 4 or the biodegradable composition according to any one of claims 6 to 8 in the preparation of biodegradable mulch films.

10. A biodegradable mulch film, characterized in that, Includes the polylactic acid block copolymer according to any one of claims 1 to 4, or the biodegradable composition according to any one of claims 6 to 8.

Citation Information

Patent Citations

  • Polyurethane resin, method for preparing same and application of polyurethane resin

    CN109575228A

  • Degradable thermoplastic polyurethane elastomer as well as preparation method and application thereof

    CN113968954A

  • Ink for solvent-free composite printing and preparation method thereof

    CN114891397A

  • Renewably derived thermoplastic polyester-based urethanes and methods of making and using the same

    US20170145145A1